An Assessment of the Contribution of Company Income Tax on the Nigerian Economic Development - Gololo, Ibrahim Aliyu (International Journal of Accounting & Finance Review, 2018)
This study examined the contribution of company’s income tax on Nigerian economic development. The study utilized secondary data sourced from Central Bank of Nigeria (CBN) Statistical Bulletin and Federal Inland Revenue Service (FIRS). The study employed Statistical packages for social science (SPSS) technique for the analysis collected data, where Natural logarithm of Gross Domestic Product (GDP), the dependent variable stands as a proxy for economic development, and Company Income Tax (CIT), stands as the independent variables. The results of the analysis showed that company income tax does not have significant and positive contribution on the Nigeria economic development from the period of 2011 to 2015. In accordance with the findings, the study recommended that government should improve the level of supervision and regulating the activities of all agencies vested with responsibility of tax collections and administration, so that same amount realized as tax to be remitted to federation. Government officials or leaders need to be transparent and accountable in public monies. Monies collected from companies inform of company income tax (CIT) should be properly channeled to developmental project to benefit the citizens. And tax authorities should design penalties for defaulting companies. And finally, Tax clearance should also be presented when an individual company’s wants to transact with government agencies.